Barriers and facilitators of HIV partner status notification in low- and lower-middle-income countries: A mixed-methods systematic review - Fatemeh Tavakoli; Mohammad Karamouzian; Ali Akbar Haghdoost; Ali Mirzazadeh; Mahlagha Dehghan; Maliheh Sadat Bazrafshani; Azam Bazrafshan; Hamid Sharifi (BMC Infectious Diseases)
Abstract Background The uptake of HIV partner status notification remains limited in low- and lower-middle-income countries. This mixed-methods systematic review aims to summarize the barriers and facilitators of HIV partner status notification in these settings. Methods We searched PubMed, Embase, CINAHL, PsychINFO, Scopus, and Web of Science from January 01, 2000, to August 31, 2023, for empirical qualitative and quantitative studies. Two independent reviewers completed the title, abstract, full-text screening, and data extraction. The risk of bias was assessed using a mixed-methods appraisal tool (MMAT), and the study findings were summarized narratively. Results Out of the 2094 studies identified, 59 relevant studies were included. Common barriers included fear of stigma and discrimination, violence, abandonment, breach of confidentiality and trust, low HIV-risk perception, and limited knowledge of HIV and HIV testing. Facilitators of HIV partner status notification were feelings of love and closeness in marital relationships, feelings of protecting self and partners, and HIV counseling services. Conclusion Efforts to improve HIV partner status notification in low- and lower-middle-income countries should consider barriers and facilitators across all its components, including notification, testing, and linkage to treatment. In addition, HIV partner services must be adapted to the unique needs of key populations.